2022
DOI: 10.1177/08902070221104628
|View full text |Cite
|
Sign up to set email alerts
|

What does a personality science approach to post-traumatic growth reveal?

Abstract: Recent research has advocated for the value of conceptualizing post-traumatic growth as positive personality change. However, most research continues to use both methodologically suspect assessment tools and unsupported theoretical assumptions. How can personality psychologists contribute to the pursuit of high-quality research on this topic? The current special issue, which grew out of the European Association for Personality Psychology (EAPP) expert meeting on “Integrating Post-Traumatic Growth and Personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The notion of adversarial growththat people learn, change, and develop in positive ways in their selves, worldviews, and relationships after adversityis a major focus of contemporary scientific scrutiny (Blackie & Jayawickreme, 2022). Research has consistently found that the positive framing of items and restricted response options in questionnairebased methods can result in inflated self-reports of adversarial growth that are not necessarily associated with adaptive outcomes (Boals & Liu, 2020;Boals & Schuler, 2018, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of adversarial growththat people learn, change, and develop in positive ways in their selves, worldviews, and relationships after adversityis a major focus of contemporary scientific scrutiny (Blackie & Jayawickreme, 2022). Research has consistently found that the positive framing of items and restricted response options in questionnairebased methods can result in inflated self-reports of adversarial growth that are not necessarily associated with adaptive outcomes (Boals & Liu, 2020;Boals & Schuler, 2018, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a considerable body of research has examined how people change as function of negative life events, such as the loss of a job, friend, or romantic partner (Bleidorn et al, 2018;Denissen et al, 2019;Lüdtke et al, 2011;Specht, 2017). However, less attention has been given to the question why people react differently to negative life events (Blackie & Jayawickreme, 2022;Bleidorn et al, 2018;Jayawickreme et al, 2020;Mangelsdorf et al, 2019). This is surprising given that findings have consistently pointed to significant individual differences in the trajectories of personality traits following negative life events (Bleidorn et al, 2020;Bleidorn et al, 2021;Denissen et al, 2019;Schwaba et al, 2022).…”
Section: Post-event Changes In Personality Traitsmentioning
confidence: 99%
“…Theories of personality development offer detailed hypotheses about selection effects of personality traits on the occurrence of life events (e.g., correspondence principle; Roberts & Nickel, 2017) as well as about socialization effects of normative life events on personality trait changes (e.g., social investment principle; Roberts et al, 2005). However, despite robust evidence that people change in different ways after experiencing a negative life event (e.g., Blackie & Jayawickreme, 2022;Bleidorn et al, 2020;Denissen et al, 2019), existing theories provide little guidance about the factors explaining individual differences in people's personality trajectories following the experience of negative life events.…”
Section: Theoretical Perspectives On Individual Differences In Post-e...mentioning
confidence: 99%
See 2 more Smart Citations